Bridging the gap between emerging models and humans by learning from polio animal studies: A systematic review. Issue 2 (22nd June 2022) - Moreni, Giulia; Aknouch, Ikrame; Ras, Morris; Brouwer, Lieke; Spijker, René; Calitz, Carlemi; Stittelaar, Koert J.; Sridhar, Adithya; Wolthers, Katja C.; Pajkrt, Dasja
Abstract: Disease modelling plays a fundamental role in biomedical research, even more in virology where the virus depends strictly on its host for replication. Although animal models are extensively used in virology, there is an increasing demand for animal‐free research. Therefore, during this transition, it is crucial to learn and take advantage of animal research to better implement new emerging models. In this study, we aim to systematically review the translation from animal models to humans for the well‐characterized viral disease polio, as a reference for novel in vitro models in virology. We found a high risk of bias in the included studies and a large diversity of animal models. Moreover, we showed that animal models for studying poliovirus pathogenesis are mainly discrimination models focusing on specific aspects of the disease allowing an insightful understanding of the complex poliovirus infection. Our review underlines the importance of proper standardization of new emerging models and a careful interpretation of the results from discrimination models. Abstract : Animal models have been extensively used in biomedical research. As we are transitioning towards animal‐free research, we can learn from the translation of results from animal models to humans in order to implement new emerging models.